Medical Spanish Graphic Activity: A MeGA Deliberate Practice Approach to Reducing Jargon Use With Spanish-Speaking Acute Care Patients - Pilar Ortega; Rafael Cisneros; Yoon Soo Park (Association of American Medical Colleges, 2024)
Introduction Medical Spanish courses in US medical schools aim to teach patient-centered communication, yet many existing resources focus on technical vocabulary and may inadvertently increase jargon use with patients. Graphic medicine presents an opportunity for interactive learning that centers the patient experience, yet it has never been explored in medical Spanish education. Methods We developed a Medical Spanish Graphic Activity (MeGA) for medical student deliberate practice of patient-centered verbal communication focused on three aspects: diagnosis, treatment, and follow-up care. Each 30-minute activity included a comics handout depicting a patient with a common problem. Students used voice-to-text technology to record their explanations in response to prompts. Transcripts were analyzed for jargon use, including total jargon, unexplained jargon, and problem words (non-Spanish words plus unexplained jargon), utilizing a previously published, reliable protocol for Spanish medical jargon classification. Participants voluntarily provided postactivity feedback. Results Twenty-nine fourth-year students with intermediate or greater Spanish skills participated in a series of 10 MeGA activities between January and April 2022. Unexplained jargon use and problem words progressively decreased for all transcripts (diagnosis, treatment, and follow-up; all ps < .001). Total jargon use also decreased, but this was not significant in follow-up transcripts (p = .38). All students agreed that MeGA helped them enhance communication skills applicable to patient care and self-identify strengths and limitations. Discussion MeGA is realistic to implement, engages students' active participation in the speaking domain, and reduces unexplained jargon use. Future studies should explore the broader application of this model and engage patient perspectives.